Guidelines for acromegaly management: an update. - Melmed, S; Colao, A; Barkan, A; Molitch, M; Grossman, AB; Kleinberg, D; Clemmons, D; Chanson, P; Laws, E; Schlechte, J; Vance, M; Ho, K; et al. (2009)
OBJECTIVE: The Acromegaly Consensus Group reconvened in November 2007 to update guidelines for acromegaly management. PARTICIPANTS: The meeting participants comprised 68 pituitary specialists, including neurosurgeons and endocrinologists with extensive experience treating patients with acromegaly. EVIDENCE/CONSENSUS PROCESS: Goals of treatment and the appropriate imaging and biochemical and clinical monitoring of patients with acromegaly were enunciated, based on the available published evidence. CONCLUSIONS: The group developed a consensus on the approach to managing acromegaly including appropriate roles for neurosurgery, medical therapy, and radiation therapy in the management of these patients.